2017
DOI: 10.1021/acs.jpcc.6b09892
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Two-Dimensional Halogen Bonded Supramolecular Networks on a Graphene/Iridium(111) Surface

Abstract: The properties of 2D supramolecular self-assemblies on surfaces depend on the fine balance between molecule-substrate and molecule-molecule interactions. In this article, we study the growth of 1,3,5-tri(4'-bromophenyl)benzene (TBB) monolayer on graphene epitaxially grown on Ir(111) by means of low temperature scanning tunneling microscopy and spectroscopy (LT-STM/STS) combined with a fully atomistic 1 description of the molecules in interaction with the Gr/Ir(111) substrate, using density functional theory (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Moreover, π-conjugated molecules can self-assemble on surfaces in various supramolecular networks which can be observed by scanning tunneling microscopy (STM). Multiscale transitions between different phases and surface organizations have already been evidenced with several systems. STM studies of conformational changes at the single-molecule level have shown cis – trans isomerization of a series of molecules such as azobenzene or stilbene derivatives. Isomerization can be induced by several inputs. Methylthiolate self-assembly and isomerization on a Au(111) surface and the direct observation of photoinduced tautomerization in single porphycene molecules on a Cu(111) surface were also recently reported. , Linear molecules can form densely close-packed or flower-like structures with cavities depending on the intermolecular interactions. ,,, Triangle-shaped molecules with different substituents form open honeycomb or flower-like structures or close-packed stripe-like structures. ,, We also demonstrated various organizations and on-surface isomerization of a ditopic ligand consisting of two coordinating 4-phenyl-2,2′-bipyridine entities linked through a central 9,9-dihexylfluorene bridge. The observed phase transitions were generated by protonation, and involved an intramolecular cis -to- trans -like isomerization, a change from weak to strong hydrogen bonding, and a structural phase transformation of gear chains into a stripe-like organization …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, π-conjugated molecules can self-assemble on surfaces in various supramolecular networks which can be observed by scanning tunneling microscopy (STM). Multiscale transitions between different phases and surface organizations have already been evidenced with several systems. STM studies of conformational changes at the single-molecule level have shown cis – trans isomerization of a series of molecules such as azobenzene or stilbene derivatives. Isomerization can be induced by several inputs. Methylthiolate self-assembly and isomerization on a Au(111) surface and the direct observation of photoinduced tautomerization in single porphycene molecules on a Cu(111) surface were also recently reported. , Linear molecules can form densely close-packed or flower-like structures with cavities depending on the intermolecular interactions. ,,, Triangle-shaped molecules with different substituents form open honeycomb or flower-like structures or close-packed stripe-like structures. ,, We also demonstrated various organizations and on-surface isomerization of a ditopic ligand consisting of two coordinating 4-phenyl-2,2′-bipyridine entities linked through a central 9,9-dihexylfluorene bridge. The observed phase transitions were generated by protonation, and involved an intramolecular cis -to- trans -like isomerization, a change from weak to strong hydrogen bonding, and a structural phase transformation of gear chains into a stripe-like organization …”
Section: Introductionmentioning
confidence: 99%
“…It is a critical limitation for our aim, since unit cells of the ordered phase in the adsorption layer usually contain a large number of molecules of large size (more than 10 atoms). However, the quantum chemistry calculations can be effectively used for the parameterization of statistical models, namely, for calculating the adsorption energies and pair interaction energies for specific molecules and surfaces, [66][67][68][69][70] e.g. e, w and D parameters for the model under consideration.…”
Section: Model and Simulation Techniquesmentioning
confidence: 99%
“…The added intermolecular/ molecular−surface interaction, the triggering conditions, and the specific environment under a microscope make on-surface reactions a different field with surprisingly novel complexes. 8,9 Scanning tunneling microscopy (STM) is employed extensively to visualize 10−17 various molecular precursors and to track the frameworks generated by on-surface reactions. 18 The reactions can therefore be investigated at a submolecular level under specific conditions in ultrahigh vacuum (UHV) or at a solid/liquid interface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The reaction is often linked to, but different from, well-known chemical reactions in solution. The added intermolecular/molecular–surface interaction, the triggering conditions, and the specific environment under a microscope make on-surface reactions a different field with surprisingly novel complexes. , …”
Section: Introductionmentioning
confidence: 99%